Statistics for Batson challenges. (10th November 2017) - Kadane, Joseph B
Abstract: In U.S. law, the Batson decision and subsequent decisions forbids the use of peremptory challenges for jury selection in ways that disproportionately eliminate cognizable classes: by race, sex, ethnicity, etc. The court designed a three-stage process: a prima facie case requires a timely objection, the identification of a cognizable class, and facts sufficient to raise an inference of discrimination. If a prima facie case is found, the side using the peremptory challenge has the opportunity of explaining its decisions, and then the court decides whether discrimination has occurred. This article addresses how statistics can be used to address the strength of evidence provided by the history of the use of peremptory challenges in a case. It contrasts two different procedures used by judges in the exercise of peremptory challenges. Frequentist and Bayesian analyses are given for both procedures, using data from a recent cases.